Chapter Performance Analysis of an Integrated Starter-Alternator- Booster for Hybrid Electric Vehicles - Jurca, Florin-Nicolae (InTechOpen, 2017)
The chapter aims to investigate the reduction of the fuel consumption of conventional vehicles using mild-hybridization and considering the New European Driving Cycle (NEDC), using two topologies of electrical machines dedicated to integrated starter-alternator-booster (ISAB) applications: directly connected to the crankshaft (called 'normal ISAB') and indirectly through the belt system (called BSAB), respectively. The behaviour of ISAB and BSAB of a hybrid electric vehicle has been investigated with a multi-domain simulation software developed in Advanced Modelling Environment for performing Simulation (AMESim).